Skills of Using the Pirls International Assessment Program in Developing Learning Competence of Students - Iqbol Valiyevna Qaynarova (Academia One Publishing, 2023)
This article talks about the methods of formation and development of students' educational competences based on the PIRLS international assessment program, and the methodology of their application.
Keywords: education; training; method; formation